Analisis Kacang Pukul Sebagai Upaya Strategi Dalam Peningkatan Kualitas - Frischa Nofrianti; Gea Ibelala (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
Peanuts are a typical snack from the city of Bagansiapiapi, the basic ingredient of which is made from peanuts. The aim of this research is to carry out an in-depth analysis of the role of peanuts as a method used in an effort to create the best results in order to get quality improvement, for this research the author using research methods (qualitative methods). This research involves a survey of industrial practitioners who apply the hitting nut technique in the context of improving product quality. The research results show that hitting nuts has become a significant approach in quality improvement strategies. The author wants this research to provide in-depth insight into the potential of peanuts as a strategic tool to achieve quality improvement goals. The practical implications of this research may be useful for organizations to better understand the dynamics of hitting nuts and design more effective strategies in improving product quality. Not only that, the author wants to make an important contribution to the quality management literature and provide a basis for further research in the development of innovative quality strategies.